2019
DOI: 10.1080/17429145.2019.1680753
|View full text |Cite
|
Sign up to set email alerts
|

The effects of indole-3-butyric acid and 6-benzyloaminopuryn on Fabaceae plants morphometrics

Abstract: The experiment was conducted to study the impact of indole-3-butyric acid (synthetic auxin) and 6-benzyloaminopuryn (synthetic cytokinin), and the mixture of these compounds on fresh and dry matter production and the number of leaves, stems, and inflorescences Medicago x varia T. Martyn and Trifolium pratense L. For the plants to be thoroughly covered, 0.2 dm 3 of spraying liquid was used per one cylinder with growth regulator concentration of 30 mg dm −3. Synthetic auxin in the form of IBA, cytokinin in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Gibberellic acid regulates the seed germination process, promotes the breakdown of seed dormancy, induction of hydrolytic enzymes α-amylase and protease and stem elongation and leaf expansion 123 . Experimental data showed that when a combination of Indole-Butyric Acid (IBA) cytokinin and gibberellic acid is used as a biostimulant on the seed of Gossypium hirsutum L. plant causes an increase in the seedling emergence percentage, leaf area, height, as well as the growth of seedlings 124 . Indole acetic acid and gibberellic acid are well-studied bacterial and fungal signalling molecules that are produced during plantmicrobe interactions as Microbial Plant Biostimulants (MPB) to boost plant growth and tolerance to abiotic stresses 125,126 .…”
Section: Plant Hormone As Biostimulantmentioning
confidence: 99%
“…Gibberellic acid regulates the seed germination process, promotes the breakdown of seed dormancy, induction of hydrolytic enzymes α-amylase and protease and stem elongation and leaf expansion 123 . Experimental data showed that when a combination of Indole-Butyric Acid (IBA) cytokinin and gibberellic acid is used as a biostimulant on the seed of Gossypium hirsutum L. plant causes an increase in the seedling emergence percentage, leaf area, height, as well as the growth of seedlings 124 . Indole acetic acid and gibberellic acid are well-studied bacterial and fungal signalling molecules that are produced during plantmicrobe interactions as Microbial Plant Biostimulants (MPB) to boost plant growth and tolerance to abiotic stresses 125,126 .…”
Section: Plant Hormone As Biostimulantmentioning
confidence: 99%